Identifying the influence of El Nino Southern Oscillation (ENSO) and Indian Ocean Dipole (IOD) Phenomena on Rainfall in The Aceh Region, Indonesia - Jannah, Miftahul; Ismail, Nazli; Asyqari, Amir; Indahsari, Fitriana N.; Abdullah, Faisal (Journal of Geoscience, Engineering, Environment, and Technology, 2024)
The interaction process between the atmosphere and the ocean that occurs in the Pacific Ocean and the Indian Ocean has a major impact on climate and weather conditions in Indonesia. The phenomenon that arises due to this interaction is known as El Nino - Southern Oscillation (ENSO). In addition to ENSO, other mechanisms also impact weather and climate change in Indonesia, including the Indian Ocean Dipole (IOD). This study aimed to analyze the effect of ENSO and IOD on rainfall in the Aceh region. The data used were CHIRPS rainfall data with the locations of four meteorological stations and one climatology station in Aceh, IOD index data and ENSO index data. Data processing in this study was carried out using Grid Analysis and Display System (GrADS) software and Spreadsheet for CHIRPS rainfall data, followed by processing ENSO index data and IOD index using Spreadsheet software. The analysis showed that the ENSO phenomenon has a longer occurrence than the IOD phenomenon. ENSO has a greater influence on rainfall in the Aceh region than IOD, especially La Nina, which has a weak to moderate correlation. Negative IOD and El Nino phenomena influence several observation points, but some stations do not show a correlation between rainfall and the index. The positive IOD phenomenon is strongly negatively correlated with rainfall at the observation station, which shows that positive IOD does not influence the Aceh region.